Circularly polarized luminescence of achiral open-shell π-radicals. Issue 46 (21st May 2019) - Jin, Qingxian; Chen, Sanxu; Sang, Yutao; Guo, Haoqing; Dong, Shengzhi; Han, Jianlei; Chen, Wenjie; Yang, Xuefeng; Li, Feng; Duan, Pengfei
Abstract : Doublet emission-based circularly polarized luminescence was successfully realized in luminescent π-radicals by applying three kinds of approaches, namely, induction by a longitudinal magnetic field, supramolecular chiral co-assembly, and doping into chiral liquid crystals. Abstract : Stable luminescent π-radicals with doublet emission have attracted growing attention for functional molecular materials. However, their chiroptical properties, particularly their doublet emission-based circularly polarized luminescence, have never been investigated. Here, we investigate the circularly polarized luminescence (CPL) properties of a series of achiral luminescent open-shell π-radicals through various chirality regulation approaches, including induction by a magnetic field, supramolecular coassembly and chiral liquid crystal encapsulation.